Large‐seeded Common Bean PRA152, PRA154, and PRA155 with High Levels of Broad‐Spectrum White Mold Resistance. Issue 3 (11th May 2017) - Singh, Shree P.; Schwartz, Howard F.; Terán, Henry; Centeno, Carlos; Otto, Kristen
Abstract : Large‐seeded common bean ( Phaseolus vulgaris L.) breeding lines (BL) PRA152 (Reg. No. GP‐304, PI 680637), PRA154 (Reg. No. GP‐302, PI 680635), and PRA155 (Reg. No. GP‐303, PI 680636) were jointly developed at the University of Idaho, Kimberly Research and Extension Center and Colorado State University, Fort Collins. The three BL possess the highest levels of broad‐spectrum white mold resistance (mean disease scores ranging from 3.0 to 3.8) than in previously available large‐seeded common bean BL, germplasm accessions, and cultivars to Sclerotinia sclerotiorum (causal agent of white mold disease) isolates ARS12D, ARS14D, ARS14M, ARS15T, CO467, ND710, and NY133. PRA152 was derived from Cornell 501/G 122//A 195/VCW 55, PRA154 was developed from VA 19/M0162//A 195/G 122, and PRA155 was selected from A 195/4/NY6020‐4/92BG‐7///M0162/I9365‐25//'ICA Bunsi'/G 122 common bean populations. All BL have a determinate upright growth habit Type I. PRA152 has dark greenish gray–colored seeds with average weight of 45.6 g 100 seed −1 . PRA154 has beige mottled seeds with 48.0 g 100 seed −1 . Seeds of PRA155 are cream with black spots, with 26.9 g 100 seed −1 . PRA154 matures in <100 d, and PRA152 and PRA155 require approximately 105 to 110 d from planting to harvest maturity in southern Idaho. White mold resistance from the three BL should be combined with other complementary sources of resistance to breed for yet higher levels and broader spectrum of resistance and/or introgressed into common bean cultivars of different market classes to combat white mold disease in the United States and elsewhere.